Three-dimensional recovery from a perspective view - Ng, Jian Rong. (2010)
This project studies the process of recovering lost information from a perspective image. A perspective image contains two-dimensional data of the object projected onto it, and this project seeks to identify the three-dimensional position of the projected object relative to the image. This is done by utilizing two theorems, namely the Perspective Theorem and the Vanishing Point Theorem. By manipulating the inputted data around these two theorems, lost data has been successfully recovered for both one point and two point perspectives. The procedure can be generalized into a recovery flowchart, and has been tested on several random objects with linear edges successfully. However, the procedure is unable to fully recover information from three point perspective images due to the imitations of the two theorems as well as objects with non-linear edges.